Star-shaped immunoglobulin-containing HPMA-based conjugates with doxorubicin for cancer therapy - Etrych, Tomás; Mrkvan, Tomás; Ríhová, Blanka; Ulbrich, Karel (Journal of controlled release, 2007)
Synthesis and preliminary anticancer activity of new star-shaped immunoglobulin-containing polymer-doxorubicin (DOX) conjugates were investigated. The polymer precursors used for the synthesis of immunoglobulin-polymer-drug conjugates are based on N-(2-hydroxypropyl)methacrylamide (HPMA) copolymers, the anticancer drug DOX is attached to the immunoglobulin-modified polymer via a pH-sensitive hydrazone linkage. Such polymer-DOX conjugates are stable in aqueous solution at pH 7.4 (pH of blood plasma) and the drug is released in mildly acid environment at pH 5-5.5 (pH in endosomes or lysosomes of target cells). Semitelechelic copolymer chains are linked to the immunoglobulin via one-point attachment to avoid branching of the conjugate observed in our earlier studied systems. The cytostatic activity of the conjugates tested on several cancer cell lines was similar to that of free DOX.HCl and correlated with the sensitivity of a particular cell line to DOX. The star-shaped conjugates containing immunoglobulin showed a significantly higher antitumor activity in vivo than immunoglobulin-free non-targeted polymer conjugates when tested in mice bearing EL4 T-cell lymphoma.
Keywords: nosiče léků; Drug Carriers; nádorové buněčné linie; Doxorubicin; Polymethacrylic Acids; Drug Screening Assays, Antitumor; Immunoglobulins; Lymphoma, T-Cell; myši inbrední C57BL; mužské pohlaví; screeningové testy protinádorových léčiv; Mice; Cell Line, Tumor; doxorubicin; kyseliny polymethakrylové; zvířata; Humans; Antibiotics, Antineoplastic; Immunoconjugates; myši; imunoglobuliny; lymfom T-buněčný; protinádorová antibiotika; imunokonjugáty; Mice, Inbred C57BL; lidé; Male; Animals